Comparison between unimodal and multimodal Physical Therapy interventions in frailty: a systematic review - Maria Simões; Patrícia Moura; Marina Nascimento; Renata Varanda; José Pompeu (Revista Brasileira de Atividade Física e Saúde)
Frailty can be defined as a biologic syndrome that results from decline in multiple systems leading to vulnerability, with poorer capacity of the organism to maintain homeostasis facing stressing events. Physical symptoms of frailty involve unintentional weight loss, decreased physical activity level, exhaustion, muscle weakness, impaired balance and gait. Together, these symptoms can compromise independence in activities of daily living. Physical Therapy can improve muscle strength, balance, gait and cardiorespiratory aptitude of frail elderly, but remains unclear what is the best intervention strategy: unimodal or multimodal interventions, with combined exercises. This systematic review aimed: (1) to compare the efficacy of unimodal and multimodal Physical Therapy interventions; (2) to analyze its effects on clinical outcomes and (3) to elucidate what is the best modality of exercise and its combination in order to improve physical symptoms and independence in frail elderly. Searches were conducted in PubMed, Medline, PEDro, Lilacs and Scielo databases. We obtained 2,579 studies and 17 were included in analysis. Studies analyzed the following clinical outcomes: mobility, muscle strength, balance, falls and fear of falling, quality of life and functional capacity. We conclude that both unimodal and multimodal interventions have potential to promote beneficial effects, but the analyzed studies have important methodological issues that negatively affect their quality. Although the beneficial effects of both interventions, the quality of studies analyzed does not allow us to generalize these effects. We suggest that new clinical trials should be conducted with a stronger methodology and according to current guidelines for randomized clinical trials.